1996
DOI: 10.1113/expphysiol.1996.sp003928
|View full text |Cite
|
Sign up to set email alerts
|

The use of coloured dye‐extraction microspheres to measure blood flow in rabbit skeletal muscle: a validation study with special emphasis on repeated measurements

Abstract: SUMMARYWe evaluated the use of coloured dye-extraction microspheres for measuring blood flow in the skeletal muscle of anaesthetized rabbits. Spheres were injected into the left atrium after sternotomy or lateral thoracotomy, or into the left ventricle via the left carotid artery. Both routes of administration produced adequate mixing of microspheres with the blood. In general, the values of flow obtained from spheres of different colour were well correlated. Resting flows were difficult to measure, owing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…Nevertheless, complete sedimentation was achieved by the use of ethanoic solutions, which presumably increased the specific gravity difference between microspheres and medium, aided by higher centrifugation speeds than used previously (van Oosterhout et al 1995;Hakkinen et al 1995;Tan et al 1997). Interestingly, while the recovery of pure coloured microspheres was similar to that obtained with FMs, in contrast to the present study the presence of tissue appeared to reduce the efficiency of recovery (Degens et al 1996).…”
Section: Biocompatibilitycontrasting
confidence: 54%
See 3 more Smart Citations
“…Nevertheless, complete sedimentation was achieved by the use of ethanoic solutions, which presumably increased the specific gravity difference between microspheres and medium, aided by higher centrifugation speeds than used previously (van Oosterhout et al 1995;Hakkinen et al 1995;Tan et al 1997). Interestingly, while the recovery of pure coloured microspheres was similar to that obtained with FMs, in contrast to the present study the presence of tissue appeared to reduce the efficiency of recovery (Degens et al 1996).…”
Section: Biocompatibilitycontrasting
confidence: 54%
“…Indeed, on injecting a much greater number of coloured microspheres in rabbits than was used in the present study, when corrected for differences in body weight, Degens et al (1996) found that < 10% of capillaries were blocked in TA and EDL muscles. Although blood flows were higher with FM than RM measurements in some tissues from rats that were separately injected with either radioactive or fluorescent microspheres, these data can be explained by seasonal differences in temperature, as the FM study was performed in summer and RM experiments in winter, and are most unlikely to reflect different microsphere quality.…”
Section: Biocompatibilitymentioning
confidence: 98%
See 2 more Smart Citations
“…Normally, resting muscle blood flow is reported to be in a range between 3-8ml/min/100 g. This blood flow is increased up to 10 times when the muscle is contracted, although the blood flow was also influenced by intramuscular pressure [2,6,8]. Although the resting blood flow in this report was higher than that in other reports, our results demonstrate that blood flow in the gluteus medius muscle decreases significantly when it has been dissected (mobilised) two-thirds from its proximal or distal origins.…”
Section: Discussionmentioning
confidence: 99%